Presence of Dactylosoma sp. in Frogs of the Telmatobius Genus Confiscated in Lima, Peru - Manrique, Miguel (2024)
Peru is a megadiverse country and ranks third in amphibian diversity. Nevertheless, 21% of its amphibian species are threatened. Telmatobius is one of the most endangered genera of this class of vertebrates, with the main threats being habitat loss and degradation, illegal trafficking, climate change, and infectious diseases. This study aimed to determine the presence of hemoparasites in seized specimens. Blood samples were collected from the ventral abdominal vein of 50 confiscated Telmatobius frogs in Lima, and blood smears were prepared and stained using Wright’s stain. Hemogregarines of the Dactylosoma genus (Dactylosomatidae family) were identified in 14% (n = 7/50) of the samples analyzed. This study represents the first report of a hemoparasite in Telmatobius.